Relationship between bacterial compartment and particulate organic matter (POM) in coastal systems: An assessment using fatty acids and stable isotopes. (5th July 2020) - Liénart, Camilla; Savoye, Nicolas; Conan, Pascal; David, Valérie; Barbier, Pierrick; Bichon, Sabrina; Charlier, Karine; Costes, Laurence; Derriennic, Hervé; Ferreira, Sophie; Gueux, Aurore; Hubas, Cédric; et al.
Abstract: Particulate organic matter (POM) in coastal systems is a mixture of different organic matter (OM) sources originating from land and sea. Among sources, bacterial biomass plays a large role in OM processing and carbon recycling in the ocean and is often neglected as a source in common approaches. The present study proposes to use elemental and isotopic ratio of carbon and nitrogen (C:N, δ 13 C, δ 15 N) and fatty acids to investigate the relationship between bacteria and surface water POM composition of three systems with different characteristics (two marine and one estuarine) over an annual cycle. Overall, our results highlight a positive relationship between bacterial contribution and continental degraded or undergoing degradation POM for all the studied systems and an inverse relationship with pelagic primary producers. At multisystem scale, high bacterial contribution is linked to high proportion of refractory terrestrial material characterizing estuarine stations whereas in marine systems, the occurrence of bacteria is mainly linked to river POM. Over the annual cycle, bacterial markers are more abundant during the winter period characterized by larger river and/or benthic POM contribution. This seasonal pattern is mainly driven by changes in river flows and resuspension. This study highlights the importance of bacterial compartment as a component of coastal and estuarine POM. Even though these results remains semi-quantitative, similar studies in other types of systems can help to understand microbial role in OM dynamic and to better estimate bacterial source in carbon budgets and food web studies. Highlights: Fatty acids, δ 13 C and δ 15 N are used to link bacterial-derived OM and POM. Bacterial OM is higher in turbid systems characterized by refractory terrestrial POM. Bacterial OM is higher in winter for seasonal systems and linked to river/benthic POM. Bacterial and degraded/in degradation OM show positive relationship for all systems.